Utilization of Mango Leaf as a Low-Cost Adsorbent for the Removal of Cu(II) Ions from Aqueous Solution - Ong, Pick-Sheen; Ong, Siew-Teng; Hung, Yung-Tse (Asian Journal of Chemistry, 2013)
The potential of mango leaves as a low-cost adsorbent for the removal of Cu(II) ions from aqueous solution was investigated in this study. The influences of pH, contact time, initial metal ions concentration, agitation rate and particle size were studied in batch experiments at room temperature. IR spectrum analysis was employed to study the functional groups of the mango leaves before and after modifications as well as after sorption process. Maximum sorption for metal ion was found to be at pH 5. The adsorption was rapid at the first 5 min of contact time and equilibrium was achieved in 60 min of agitation. Kinetic studies showed good correlation coefficient for a pseudo-second order kinetic model. The uptake was found to increase with higher agitation rate and smaller size of adsorbent. Langmuir and Freundlich, isotherm models were applied to describe the biosorption of Cu(II) ions onto mango leaves. Maximum sorption capacities calculated from the Langmuir model is 15.77 mg/g. The results showed that mango leaves have the potential to be applied as alternative low-cost biosorbent in the remediation of heavy metal contamination in wastewater.